EVALUATING USER ENGAGEMENT AND READING BEHAVIOR ASPECTS OF WEB VISITORS BY ANALYZING INDICATORS ON GOOGLE ANALYTICS DATA - Ramadhani, Shumaya Resty (LPPM Nusa Mandiri, 2022)
Nowadays, web-based technology is used as a source of information and marketing, one of which is educational institutions. This development unintentionally changes people's reading patterns, from paper to online media. However, user engagement and reading behavior on a web-based system is often overlooked while developing the plan. Understanding these two pillars can help the improvement process become more effective. Politeknik Caltex Riau has an official website that provides information about campus life and an introduction to study programs for prospective students. The information provided is quite complete and precise, yet there are many repeated questions. One example is the web visitors who are interested and asks about the registration steps, but the info is clearly on the website. Therefore, it is necessary to evaluate the understanding of the demographics, engagement, behavior, and events by implementing Google Analytics on the website. From the results, it is known that the visitors are on target. The majority of readers are high schoolers who are actively looking for university information. Many of them use smartphones to surf the website, though it is recognized that most readers do not read the content thoroughly. It can be seen from the total scroll event, which is only high at the beginning and keep decreasing while scrolling down the page. But the bounce and sessions number ​​keep rising. This phenomenon shows that the reader's engagement with the content is shallow, and reading comprehension is vague. In addition, there is also an indication of the effect of smaller screen size with the web design model as one of the reasons for the high jump rate. Thus, further studies can focus on deepening and evaluating web design and evaluating more indicators provided on Google Analytics.